The cis-lycopene isomers composition in supercritical CO2 extracted tomato by-products. (November 2017) - Urbonaviciene, Dalia; Viskelis, Pranas
Abstract: The use of concentrated carotenoid extracts from red-ripe tomato by-products in traditional foods can improve the functional properties of the product while increasing the efficiency of industrial red-ripe tomatoes processing. In red tomatoes, lycopene is almost exclusively found in the all- trans -form, but during processing lycopene can undergo isomerisation to cis -lycopene isomers. The cis -lycopene isomers offer potentially better health benefits than the trans -lycopene isomers. The objectives of this study were to optimize supercritical carbon dioxide (SC-CO2 ) extraction parameters for the isolation of the non-polar tomato by-product fraction (oleoresin) and cis -lycopene isomers by using a central composite rotatable design (CCD) model with response surface methodology (RSM). SC-CO2 using CCD and RSM was used for the first time for the isolation of cis -lycopene isomers from tomato by-products. The best results in terms of oleoresin yield were obtained at a temperature of 73.9 °C, a pressure of 53.7 MPa and a time of 155 min, whereas the optimal extraction process parameters of cis -lycopene isomers are a 52 °C temperature, a 55 MPa pressure and a 180 min extraction time. The optimized conditions of SC-CO2 allows to obtain high yields of lycopene rich extracts (oleoresins) comprising higher percentage of cis -lycopene isomers (∼62% of total lycopene). Highlights: Tomato by-products oleoresin was extracted using supercritical CO2 . Optimal conditions for cis -lycopene isomers extraction was determined. Full factorial design was used to understand the effect of process variables. The optimum conditions were 52 °C, 55 MPa and 180 min.